8x+3=-2x-7

Simple and best practice solution for 8x+3=-2x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x+3=-2x-7 equation:


Simplifying
8x + 3 = -2x + -7

Reorder the terms:
3 + 8x = -2x + -7

Reorder the terms:
3 + 8x = -7 + -2x

Solving
3 + 8x = -7 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
3 + 8x + 2x = -7 + -2x + 2x

Combine like terms: 8x + 2x = 10x
3 + 10x = -7 + -2x + 2x

Combine like terms: -2x + 2x = 0
3 + 10x = -7 + 0
3 + 10x = -7

Add '-3' to each side of the equation.
3 + -3 + 10x = -7 + -3

Combine like terms: 3 + -3 = 0
0 + 10x = -7 + -3
10x = -7 + -3

Combine like terms: -7 + -3 = -10
10x = -10

Divide each side by '10'.
x = -1

Simplifying
x = -1

See similar equations:

| 2(y/3-y/5)=3+y/10 | | 2x+1=-5x-13 | | g/2+g+g/4=(2g-1)/12+8 | | 1x(105/(35/7)) | | 7L=41 | | 8L=41 | | 4L=41 | | h-5(h+6)=7(h/3-8) | | X^2+5x+m=0 | | 57.85=1.75+3.6+d | | 57.85=3.6+1.75xd | | 57.85=1.75+3.6xd | | 2L=46 | | 5L=46 | | 6L=46 | | 4l=46 | | 66.55=1.8+1.75*d | | 66.55=1.75+1.8+d | | 13/x=30/42 | | d=66.55-1.75-1.8 | | F(x)=x^3+3x^2 | | 20=6(y-6)+2y | | 50=r+8 | | 50=r+r-8 | | 50-8=r | | 50-8=2r | | X/23=15/33 | | x-11=17-3x | | X/22 | | -7y-21=0 | | c=18+3c | | 5d=40-5d |

Equations solver categories